2013
DOI: 10.1080/01443410.2013.792331
|View full text |Cite
|
Sign up to set email alerts
|

Examining the mediating effect of learning strategies on the relationship between students’ history interest and achievement

Abstract: Research into the effect of interest consistently indicated that interest positively related to students' achievement; however, the mechanism through which it affected the learning result remained an open question. This study intended to examine how learning strategies mediated the relationship between interest and achievement in the domain of history learning. Biggs Learning Process Questionnaire, which distinguishes between the surface and deep-level learning strategies, was adopted to describe students' lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
1
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 64 publications
2
7
1
2
Order By: Relevance
“…Hal serupa pun diungkapkan oleh Renninger, Hidi, & Krapp (2014) bahwa ada beberapa hal yang menggambarkan minat belajar siswa, seperti adanya perhatian dan konsentrasi yang lebih besar, perasaan senang untuk belajar, dan adanya peningkatan kemauan untuk belajar. Selain itu, Dan & Tod (2014) mengungkapkan bahwa siswa yang memiliki minat belajar memiliki perasaan tersendiri seperti:…”
Section: Indikator Minat Belajarunclassified
“…Hal serupa pun diungkapkan oleh Renninger, Hidi, & Krapp (2014) bahwa ada beberapa hal yang menggambarkan minat belajar siswa, seperti adanya perhatian dan konsentrasi yang lebih besar, perasaan senang untuk belajar, dan adanya peningkatan kemauan untuk belajar. Selain itu, Dan & Tod (2014) mengungkapkan bahwa siswa yang memiliki minat belajar memiliki perasaan tersendiri seperti:…”
Section: Indikator Minat Belajarunclassified
“…Still others reported a negative relationship between surface learning and academic achievement, but no relationship between deep learning and academic achievement (Dan & Todd, 2014;Thomas & Gadbois, 2007).…”
Section: Study Approaches To Learningmentioning
confidence: 99%
“…In this respect, Dan and Todd (2014) examined the relationship between history learning approaches and the history interests of students, and they found that there was a negative correlation between interest and surface learning and a positive correlation between interest and deep learning.…”
Section: Study Approaches To Learningmentioning
confidence: 99%
“…Previous studies on this subject provided similar results regarding the interaction between learning strategies and achievement and attitudes, although in different fields. For example, Dan and Todd (2013) found that the interest of students in the history course, and the learning strategies employed by them, had an effect on their achievement. Similarly, Ames and Archer (1988) stated that those students who focused on success were the students employing more effective strategies and having positive attitudes towards the course.…”
Section: Discussionmentioning
confidence: 99%